The Nutrient Content as Indicator of the Validity of Fish as a Healthy Food Source - Iqbal, Muhammad Naeem; Ashraf, Asfa (PSM Biological Research, 2025)
Environmental deterioration and starvation, in all its manifestations, are spreading at a rapid pace over the planet. Poor diets combined with unsustainable food systems might be regarded one of the key contributors to these worldwide problems. Fish is typically recognized as a healthy food item as indicated by its nutritional content. In this issue, Shamsan et al. (2025) investigated nutritional value of a commercial fish species, Platycephalus indicus. The values of moisture, protein, ash, and fat content reflect its nutritional value for humans, which suggest that this type of fish is suitable for usage as a nutritious food item. Thus, nutritional content may be exploited to determine the quality of fish products as a healthy food source.